Increased THC, DHC, PA and Survival of White Shrimp (Litopenaeus vannamei) by Feeding Porphyridium cruentum Nanoparticle - Saniya Lailatul Qodriyah; Satyantini, Woro Hastuti; Nova Erika; Laksmi Sulmartiwi (Department of Aquaculture, 2025)
A common disease in white shrimp is vibriosis which can cause acute hepatopancreatic necrosis or Acute Hepatopancreatic Necrosis Disease (AHPND). Immunostimulants are one of the alternatives to defend against pathogen infection. Porphyridium cruentum is a natural substance that can be used as an immunostimulant. The development of nanotechnology is progressing rapidly today due to its important role in various fields. The use of P. cruentum nanoparticles enhances the absorption and efficiency of feed, making their application more effective. The purpose of this study is to determine the effect of the addition of P.cruentum nanoparticles in feed on the enhancement of the immune response of white shrimp after administration for one month of rearing. Shrimp were divided into four groups, one group was not fed with P.cruentum nanoparticles (K), three other groups were fed with P.cruentum nanoparticles 0.8; 1.0; 1.2% per kg of feed respectively. The results showed that the treatment with the addition of P.cruentum nanoparticles provided an increase in Total Hemocytes Count (THC), Differential Hemocyte Cells (DHC), and phagocytic activity (PA) after administration for one month of rearing and at the end of rearing provided a higher survival rate than the control.